Radiotherapy for age related macular degeneration causes transient lens transparency changes. Issue 7 (1st July 2000) - Eter, Nicole; Wegener, Alfred; Schüller, Heinrich; Spitznas, Manfred
Abstract : AIM: Evaluation of potential side effects of photon radiotherapy on the transparency of the lens. METHODS: The anterior segments of 14 phakic eyes from patients suffering from subfoveal neovascularisation as a result of age related macular degeneration (AMD) were documented by Scheimpflug photography (Topcon SL-45, Kodak Tmax 400) before the start of radiotherapy as well as 6 and 12 months afterwards. All negatives were evaluated by microdensitometry, and peak heights for distinct layers of the lens were used for statistical comparison. External beam radiotherapy (6 MeV photons) consisted of a total dose of 20 Gy, delivered as 10 fractions of 2 Gy. RESULTS: Six and 12 months following irradiation statistical comparison of the ratios in density change of lenses from irradiated versus non-irradiated fellow eyes revealed statistically significant (p⩽0.05) loss of transparency of layers 5 and 7 of the nuclear region. In layer 1 (capsuloepithelial complex) the changes were close to significance. At the 12 month examination, however, all of these significant changes had disappeared. CONCLUSION: Six months following radiotherapy for AMD, both the anterior capsuloepithelial region and the nuclear layers showed precataractous changes. As most of these significant differences had disappeared after 12 months, it is obvious that these findings reflect acute radiation damage to the lens epithelial cells and an ionising effect on the proteins of the lens nucleus. Long term studies will have to be carried out to demonstrate whether or not this acute radiation damage, which is expressed as a transient increase in light scattering of some layers of the lens, actually does lead to permanent transparency changes, thus reflecting radiation cataractogenesis, and if so, after what time interval and to what extent cataract occurs.